Chemical constituents from pericarp of garcinia mangostana linn / Siti Aisyah Mohamed Azlan - Mohamed Azlan, Siti Aisyah (Faculty of Applied Sciences, 2016)
Garcinia mangostana L. is a tropical tree from Southeast Asia and its fruit pericarp is a well-known traditional medicine. Extraction and isolation were carried out by chromatographic and spectroscopic technique respectively. A hexane extract of Garcinia mangostana L. pericarp shows abundant of xanthones compounds and three xanthones that being identified and elucidated their structure were a-mangostin (4), p-mangostin (12) and garcinone D (39). Their structures were elucidated on the basis of IR, UV, NMR and MS spectroscopic data, in addition to comparison with literature data.